Rice variety donors for tolerance to Fe toxicity in West-Africa - CGIAR Research Program on Rice (2021)
Selected donors for tolerance to Fe toxicity in West-Africa among interspecific O sativa x O. glaberrima lines of a QTL mapping population. Donors have been shared with counterparts in Madagascar for confirmation of tolerance and initiation of a breeding populations in crosses with local varieties.